Environment impact of a concentrated solar power plant - Bošnjaković, Mladen; Tadijanović, Vlado (2019)
More recently, there has been an increasing interest in the use of concentrated solar thermal energy for the production of electricity, but also for the use in cogeneration and trigeneration. In this sense, the increasing use of solar thermal energy in urban areas is expected, and its impact on the environment is inducing an increasing interest. The paper analyses the impact of concentrated solar power technology (linear Fresnel, parabolic trough, parabolic dish, and central tower) on the environment in terms of water consumption, land use, wasted heat, emissions of gases, emissions of pollutants that include the leakage of heat transfer fluid through pipelines and tanks, impact on flora and fauna, impact of noise and visual impact. The impact on the environment is different for different concentrated solar power technologies and depends on whether thermal energy storage is included in the plant. Water is mainly used for cooling the system, but also for cleaning the surface of the mirror. To reduce water consumption, other cooling technologies (e.g. air cooling) are being developed. The available data from the literature show large variances depending on the size of the plant, geographic location and applied technology.
Bibliografija: 16 jed.
Abstract.
Keywords: Solarne elektrane -- Utjecaj na okoliš